Soft tissue repairing and wrinkle filling material based on N-vinylpyrrolidone and polyethylene glycol diacrylate mixed polymer hydrogel and preparation process thereof

Through the photothermal dual initiation system of N-vinylpyrrolidone and polyethylene glycol diacrylate mixed hydrogel, the problems of fast degradation rate and insufficient mechanical strength of traditional soft tissue filling materials are solved, and safe and efficient hydrogel preparation is achieved, which is suitable for soft tissue repair and wrinkle filling.

CN120789335APending Publication Date: 2025-10-17梁杰
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510867575.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-26
Publication Date
2025-10-17

AI Technical Summary

Technical Problem

Existing soft tissue filling materials have a fast degradation rate, insufficient mechanical strength and potential biosafety risks, resulting in a short-lasting filling effect. Traditional hydrogels also have the problem of toxic monomer residues.

Method used

A mixed hydrogel based on N-vinyl pyrrolidone and polyethylene glycol diacrylate was prepared by polymerization under mild conditions through a dual light and heat initiation system, combined with dialysis and sterilization treatment, to prepare a hydrogel with adjustable mechanical strength and degradation cycle.

Benefits of technology

It achieves rapid polymerization under mild conditions, precisely controls the elastic modulus and degradation cycle of the hydrogel, significantly reduces the residual monomer content, improves the safety and adaptability of the material, and meets the needs of different applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120789335A_ABST
    Figure CN120789335A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of biomedical materials, and discloses a soft tissue repairing and wrinkle filling material based on N-vinylpyrrolidone and polyethylene glycol diacrylate mixed polymer hydrogel and a preparation process of the soft tissue repairing and wrinkle filling material based on N-vinylpyrrolidone and polyethylene glycol diacrylate mixed polymer hydrogel. Polyethylene glycol diacrylate; an initiator; a solvent; the preparation process comprises the following steps: S1, mixing and dissolving all materials to form a pre-polymerization solution; s2, forming hydrogel through photopolymerization and thermal polymerization; s3, carrying out dialysis on the obtained hydrogel; and S4, performing freeze drying on the dialyzed hydrogel, and performing sterilization treatment. By adopting a light and heat dual initiation system, the purpose of realizing rapid polymerization under a mild condition is achieved. Compared with a single initiation system in the prior art, the technology solves the problems of slow polymerization rate and harsh reaction conditions, so that the polymerization process is more efficient and safer.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of biomedical materials, in particular to a soft tissue repair and wrinkle filling material based on N-vinyl pyrrolidone and polyethylene glycol diacrylate mixed polymer hydrogel and a preparation process thereof. BACKGROUND

[0002] The currently commonly used soft tissue filling materials mainly include hyaluronic acid and collagen. These materials are widely used in the fields of beauty and medicine due to their good biocompatibility and clinical operability. Hylauronic acid, as a naturally occurring polysaccharide in the body, is favored due to its excellent moisturizing effect and biocompatibility; collagen is widely used due to its support effect on skin structure.

[0003] Although these traditional filling materials have advantages to some extent, they generally have problems such as fast degradation rate, insufficient mechanical strength, and short effect. The effect of hyaluronic acid can usually only be maintained for a few months, and the structural strength of collagen often cannot meet the application scenarios with high demand, resulting in that the filling effect cannot be maintained. In addition, traditional hydrogels (such as polyacrylamide systems) will leave toxic monomers, and the degradation products also have potential biological risks, which limit their wide application in the clinic. SUMMARY

[0004] In view of the deficiencies of the prior art, the present application provides a soft tissue repair and wrinkle filling material based on N-vinyl pyrrolidone and polyethylene glycol diacrylate mixed polymer hydrogel and a preparation process thereof, which solves the problems of fast degradation rate, insufficient mechanical strength, and potential biological safety risk of existing soft tissue filling materials.

[0005] To achieve the above purpose, the present application is realized by the following technical scheme: a soft tissue repair and wrinkle filling material based on N-vinyl pyrrolidone and polyethylene glycol diacrylate mixed polymer hydrogel, comprising the following component materials in mass fraction:

[0006] N-vinyl pyrrolidone 10-25 parts;

[0007] Polyethylene glycol diacrylate 1-10 parts;

[0008] Initiator 0.1-1 parts;

[0009] Solvent 60-150 parts.

[0010] Preferably, the concentration of N-vinyl pyrrolidone is 10-25%, and the molecular weight of polyethylene glycol diacrylate is 400-2000, and the concentration is 1-10%.

[0011] Preferably, the initiator includes a photo initiator and a thermal initiator, the photo initiator is Irgacure-2959, the thermal initiator is ammonium persulfate, and the mass ratio between the photo initiator and the thermal initiator is 1-2:0.5-1.

[0012] Preferably, the solvent can be deionized water or phosphate buffer.

[0013] The preparation process of the soft tissue repair and wrinkle filling material based on N-vinyl pyrrolidone and polyethylene glycol diacrylate mixed polymeric hydrogel includes the following steps:

[0014] S1, dissolving NVP, PEGDA and initiator in deionized water or phosphate buffer, adjusting pH to 6.5-7.5 to form a pre-polymer solution;

[0015] S2, forming a hydrogel by dual initiation polymerization of photo polymerization and thermal polymerization;

[0016] S3, dialyzing the obtained hydrogel in deionized water or phosphate buffer for not less than 72 hours to remove unreacted monomers;

[0017] S4, freeze-drying the dialyzed hydrogel and sterilizing the hydrogel;

[0018] Further, in the preparation process, N-vinyl pyrrolidone (NVP) is used as the main monomer first, NVP has excellent hydrophilicity and biocompatibility, and can provide good hydration and support function after the formation of the hydrogel. The polymer chain structure formed after the polymerization of NVP has adjustable mechanical strength and elasticity, which enables the hydrogel to adapt to different application requirements, and promotes the adhesion, proliferation and differentiation of cells, thereby improving the effect of soft tissue repair. This feature is the innovation of the present application, which has wide application potential in the field of biomedical materials.

[0019] Polyethylene glycol diacrylate (PEGDA) is used as a crosslinking agent to form a three-dimensional network structure by co-polymerization with NVP. The introduction of PEGDA in the hydrogel can increase the crosslinking density of the material, thereby enhancing the mechanical properties of the hydrogel. At the same time, due to the good hydrophilicity of PEGDA, the hydration of the hydrogel can be further improved, and the release of drugs or cells can be promoted. This crosslinking mechanism is an important innovation point of the present application, and by optimizing the molecular weight and proportion of PEGDA, the physical and biological properties of the hydrogel can be effectively regulated.

[0020] The selection and ratio of the photoinitiator (Irgacure-2959) and the thermal initiator (ammonium persulfate) in the polymerization reaction have a decisive influence on the rate of the polymerization reaction and the microstructure of the hydrogel. The photoinitiator generates free radicals under ultraviolet light irradiation, rapidly initiating the polymerization reaction of NVP and PEGDA to form a stable cross-linked network. This mechanism enables the hydrogel of the present application to be quickly positioned and fixed under mild conditions, while avoiding the degradation of biological materials caused by high temperature.

[0021] The thermal initiator (APS) generates active free radicals at a certain temperature, further promoting the cross-linking and polymerization reaction, and is particularly suitable for use in environments where photoinitiation conditions are not convenient. Due to the synergistic effect of using two initiators, the present application can flexibly adjust the polymerization conditions in different application scenarios, thereby realizing the controllability and adaptability of the material properties, which is another innovation point of the present application.

[0022] Finally, after preparation, sterilization treatment is carried out using gamma rays or ethylene oxide to ensure the safety of the hydrogel in clinical application. Gamma rays directly destroy the DNA of microorganisms through their high energy, rendering them unable to reproduce, thereby effectively sterilizing; while ethylene oxide reacts with the proteins and DNA of microorganisms through gas permeation, achieving sterilization effect. The combination of these two sterilization methods not only ensures the effective sterilization of the material, but also maximizes the preservation of the physical and chemical properties of the material, ensuring the biocompatibility and safety of the hydrogel.

[0023] Preferably, in the S2 step, the photo-polymerization is specifically: irradiating the prepolymer solution with ultraviolet light with a wavelength of 300-400 nm and an intensity of 10-50 mW / cm 2 for 1-10 minutes to initiate the polymerization reaction;

[0024] The thermal polymerization is specifically: heating the prepolymer solution to 50-70℃ through a heating furnace, and reacting for 1-4 hours to initiate the polymerization reaction.

[0025] Preferably, in the S4 step, freeze-drying is carried out below -40℃, and the drying time is 24-48 hours;

[0026] The sterilization treatment includes:

[0027] Sterilization treatment by damaging the DNA of microorganisms through gamma rays;

[0028] Sterilization treatment by injecting ethylene oxide in a sealed space.

[0029] Application of soft tissue repair and wrinkle filling material based on N-vinyl pyrrolidone and polyethylene glycol diacrylate mixed polymer hydrogel in soft tissue defect repair and skin wrinkle filling.

[0030] The application provides a soft tissue repair and wrinkle filling material based on N-vinyl pyrrolidone and polyethylene glycol diacrylate mixed polyhydrogel and a preparation process thereof.

[0031] 1、The application achieves rapid polymerization under mild conditions by using a dual initiation system of light and heat. Compared with the single initiation system in the prior art, this technology solves the problems of slow polymerization rate and harsh reaction conditions, making the polymerization process more efficient and safe.

[0032] 2、The application precisely controls the elastic modulus and degradation period of the hydrogel by adjusting the ratio of NVP to PEGDA. Compared with traditional methods, this technology can flexibly adjust the mechanical properties and biodegradation time of the hydrogel according to actual needs, avoiding application limitations caused by mismatched properties.

[0033] 3、The application effectively controls the residual monomer content to be less than 0.1% by using an in-vitro washing process. Compared with existing hydrogel preparation technologies, this innovation significantly improves the safety of the hydrogel, reduces the potential risk to the human body, and ensures the reliability in medical applications. BRIEF DESCRIPTION OF DRAWINGS

[0034] Figure 1 The preparation process flowchart of the application. DETAILED DESCRIPTION

[0035] The technical solutions in the embodiments of the application will be described below with reference to the drawings in the specification of the application. Obviously, the described embodiments are only a part of the embodiments of the application, not all embodiments. Based on the embodiments in the application, all other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the application.

[0036] Please refer to the attached Figure 1 :

[0037] Embodiment 1:

[0038] Material composition:

[0039] N-vinyl pyrrolidone (NVP): 10 parts;

[0040] Polyethylene glycol diacrylate (PEGDA): 1 part;

[0041] Photoinitiator (Irgacure-2959): 0.1 part;

[0042] Solvent (deionized water): 60 parts;

[0043] Preparation steps:

[0044] Dissolve 10 parts of NVP, 1 part of PEGDA and 0.1 part of Irgacure-2959 in 60 parts of deionized water, adjust the pH to 6.5-7.5 to form a prepolymer solution.

[0045] Irradiate the prepolymer solution with ultraviolet light with a wavelength of 300 nm and an intensity of 10 mW / cm 2 for 5 minutes to initiate polymerization to form a hydrogel.

[0046] Dialyze the obtained hydrogel in deionized water for not less than 72 hours to remove unreacted monomers.

[0047] Freeze-dry the hydrogel after dialysis, which is carried out below -40℃, and the drying time is 24 hours.

[0048] Perform sterilization treatment by destroying microbial DNA through γ-rays.

[0049] Example 2:

[0050] Material composition:

[0051] N-vinyl pyrrolidone (NVP): 17.5 parts;

[0052] Polyethylene glycol diacrylate (PEGDA): 5 parts;

[0053] Photoinitiator (Irgacure-2959): 0.5 parts;

[0054] Solvent (phosphate buffer): 100 parts;

[0055] Preparation steps:

[0056] Dissolve 17.5 parts of NVP, 5 parts of PEGDA and 0.5 parts of Irgacure-2959 in 100 parts of phosphate buffer, adjust the pH to 6.5-7.5 to form a prepolymer solution.

[0057] Irradiate the prepolymer solution with ultraviolet light with a wavelength of 350 nm and an intensity of 30 mW / cm 2 and heat the furnace to 55℃ at the same time to continuously initiate double polymerization to form a hydrogel, and the reaction time is 7 minutes.

[0058] Dialyze the obtained hydrogel in phosphate buffer for not less than 72 hours to remove unreacted monomers.

[0059] Freeze-dry the hydrogel after dialysis, which is carried out below -40℃, and the drying time is 36 hours.

[0060] Perform sterilization treatment by injecting ethylene oxide in a sealed space.

[0061] Example 3:

[0062] Material composition:

[0063] N-vinyl pyrrolidone (NVP): 25 parts;

[0064] Polyethylene glycol diacrylate (PEGDA): 10 parts;

[0065] Photoinitiator (Irgacure-2959): 1 part;

[0066] Solvent (deionized water): 150 parts;

[0067] Preparation steps:

[0068] Dissolve 25 parts of NVP, 10 parts of PEGDA and 1 part of Irgacure-2959 in 150 parts of deionized water, adjust the pH to 6.5-7.5 to form a prepolymer solution.

[0069] The prepolymer solution is heated to 70°C by simultaneously using ultraviolet light with a wavelength of 400 nm and an intensity of 50 mW / cm 2 and a heating furnace to initiate a double polymerization reaction to form a hydrogel, and the reaction time is 10 minutes.

[0070] The obtained hydrogel is dialyzed in deionized water for not less than 72 hours to remove unreacted monomers.

[0071] The dialyzed hydrogel is freeze-dried below -40°C, and the drying time is 48 hours.

[0072] Sterilization treatment is performed by destroying microbial DNA through γ-rays.

[0073] Example 4:

[0074] Material composition:

[0075] N-vinyl pyrrolidone (NVP): 25 parts;

[0076] Polyethylene glycol diacrylate (PEGDA): 10 parts;

[0077] Thermal initiator (ammonium persulfate): 0.5 parts;

[0078] Solvent (phosphate buffer): 150 parts;

[0079] Preparation steps:

[0080] Dissolve 25 parts of NVP, 10 parts of PEGDA and 0.5 parts of ammonium persulfate in 150 parts of phosphate buffer, adjust the pH to 6.5-7.5 to form a prepolymer solution.

[0081] by using both ultraviolet light irradiation with a wavelength of 400 nm and an intensity of 50 mW / cm 2 The prepolymer solution was heated to 65°C by using both ultraviolet light irradiation with a wavelength of 400 nm and an intensity of 50 mW / cm

[0082] The obtained hydrogel was dialyzed in a phosphate buffer for not less than 72 hours to remove unreacted monomers.

[0083] The dialyzed hydrogel was freeze-dried at -40°C or below for 48 hours.

[0084] Sterilization was performed by injecting ethylene oxide into a closed space.

[0085] Comparative Example 1:

[0086] Compared with Example 1, the difference is that the light / heat dual initiation system is cancelled, and only a photoinitiator (Irgacure-2959) is used for polymerization, and the rest is the same.

[0087] Comparative Example 2:

[0088] Compared with Example 1, the difference is that the ratio of NVP to PEGDA is not within the range, specifically NVP:PEGDA = 9:1 (the ratio is too low), and the rest is the same.

[0089] Comparative Example 3:

[0090] Compared with Example 1, the difference is that no dialysis treatment is performed, so the residual monomer content is higher than 0.1%, and the rest is the same.

[0091] Comparative Experiment:

[0092] Experiment 1:

[0093] Purpose of the experiment:

[0094] Comparing the polymerization rate and physical properties of the hydrogel in Example 1 (using a light / heat dual initiation system) and Comparative Example 1 (using only a photoinitiator) to verify the innovation and effectiveness of the light / heat dual initiation system.

[0095] Materials for the experiment:

[0096] N-vinyl pyrrolidone (NVP);

[0097] Polyethylene glycol diacrylate (PEGDA);

[0098] Photoinitiator (Irgacure-2959);

[0099] Thermal initiator (ammonium persulfate);

[0100] Deionized water;

[0101] Dynamic mechanical analyzer (DMA);

[0102] Experimental procedure:

[0103] Material preparation:

[0104] The required NVP, PEGDA and initiator were weighed and two pre-polymer solutions were prepared according to the formulation of Example 1 and Comparative Example 1.

[0105] Example 1: 10 parts of NVP, 1 part of PEGDA, 0.1 part of Irgacure-2959 and 60 parts of deionized water.

[0106] Comparative Example 1: 10 parts of NVP, 1 part of PEGDA and 0.1 part of Irgacure-2959 (without thermal initiator), 60 parts of deionized water.

[0107] pH adjustment:

[0108] The pH of the two pre-polymer solutions was adjusted to 6.5-7.5 to ensure optimal conditions for the polymerization reaction.

[0109] Polymerization reaction:

[0110] For Example 1, the pre-polymer solution was simultaneously exposed to ultraviolet light with a wavelength of 300-400 nm (intensity of 10-50 mW / cm 2 ) and heated to 60°C at the same time, maintaining the polymerization reaction for 5 minutes.

[0111] For Comparative Example 1, only the pre-polymer solution was irradiated with the same ultraviolet light for 5 minutes without heating.

[0112] Hydrogel preparation:

[0113] After the polymerization was complete, the sample was cooled and the total time from the start of the polymerization reaction to the formation of the hydrogel was recorded.

[0114] Physical property testing:

[0115] The dynamic mechanical analyzer (DMA) was used to measure the elastic modulus of the two hydrogels. During testing, the sample was placed in the DMA, a strain was applied and the stress response was recorded.

[0116] Data recording and analysis:

[0117] The polymerization time and elastic modulus data were collected and tabulated for comparative analysis (see Table 1 for details).

[0118] Table 1

[0119]

[0120]

[0121] Experiment summary:

[0122] In the experiment of Example 1, a dual-initiation system of light / heat was adopted for the polymerization of hydrogel, ensuring rapid polymerization under mild conditions. The mechanism of this system is based on the generation of free radicals by a photoinitiator (such as Irgacure-2959) under ultraviolet light irradiation, activating the polymerization reaction. At the same time, the addition of a thermal initiator (such as ammonium persulfate) can further promote the generation of free radicals, enhancing the rate and efficiency of the polymerization reaction. This dual-initiation mechanism makes the formation of hydrogel more rapid and homogeneous, avoiding the problems of incomplete reaction and excessive time that may be caused by the single use of light or heat initiators.

[0123] In the polymerization reaction, the interaction between N-vinyl pyrrolidone (NVP) and polyethylene glycol diacrylate (PEGDA) occurs through a free radical polymerization mechanism. The initiated free radicals react with the double acrylate groups of NVP or PEGDA to form polymer chains. By adjusting the ratio of NVP to PEGDA, the crosslinking density of the polymer can be precisely controlled, thereby realizing the customization of the elastic modulus of the hydrogel, ranging from 10 to 100 kPa. This control ability provides great flexibility for different application scenarios (such as soft tissue repair and wrinkle filling), meeting the requirements of hydrogel mechanical properties under different biological conditions.

[0124] In addition, experimental results show that after in vitro dialysis treatment, the residual monomer content in the hydrogel is significantly reduced, ensuring the biological safety of the material. The removal mechanism of residual monomers mainly relies on the hydrophilicity of the hydrogel internal structure and the material diffusion during dialysis, causing the loss of unreacted monomers with water. After more than 72 hours of dialysis treatment, the residual monomer content of the hydrogel in Example 1 is less than 0.1%, showing its safety in biomedical applications. This achievement not only meets the strict standards of clinical application for material safety, but also provides strong support for the future use of hydrogel in human medical treatment.

[0125] Experiment 2:

[0126] Purpose of the experiment:

[0127] Compare the physical properties of hydrogels in Example 1 (NVP and PEGDA are reasonably proportioned) and Comparative Example 2 (NVP and PEGDA are not in the range of proportions) including elastic modulus and degradation period to verify the precise control ability of hydrogel properties by adjusting the proportion.

[0128] Materials for the experiment:

[0129] N-vinyl pyrrolidone (NVP);

[0130] Polyethylene glycol diacrylate (PEGDA);

[0131] Photoinitiator (Irgacure-2959);

[0132] Thermal initiator (ammonium persulfate);

[0133] Deionized water;

[0134] PBS (phosphate buffered saline) solution;

[0135] Dynamic mechanical analyzer (DMA);

[0136] Experimental procedure:

[0137] Material preparation:

[0138] Prepare one hydrogel (NVP:PEGDA = 10:1) in the same ratio as Example 1.

[0139] Prepare another hydrogel (NVP:PEGDA = 9:1) in the same ratio as Comparative Example 2.

[0140] pH adjustment:

[0141] Adjust the prepolymer solution of Example 1 to pH 6.5-7.5.

[0142] Adjust the prepolymer solution of Comparative Example 2 to the same pH 6.5-7.5.

[0143] Polymerization:

[0144] For Example 1, polymerize for 5 minutes under the condition of using both UV light with a wavelength of 300-400 nm and heating to 60°C.

[0145] For Comparative Example 2, use only the same UV light condition, do not perform thermal polymerization, and also maintain for 5 minutes.

[0146] Hydrogel preparation:

[0147] After polymerization is complete, cool the sample and take out the hydrogel.

[0148] Elastic modulus test:

[0149] Measure the elastic modulus of both hydrogels using a dynamic mechanical analyzer (DMA).

[0150] Degradation experiment:

[0151] Soak the hydrogel sample in a PBS solution and perform a degradation test at 37°C, periodically sample, and record the remaining mass at the time point.

[0152] The mass change of two kinds of hydrogels at 0, 1, 2, 4, 6, 8 weeks was monitored, and the degradation period was calculated.

[0153] Data recording and analysis:

[0154] The numerical value of the elastic modulus and the sample mass data of the degradation period were collected and tabulated for comparative analysis (see Table 2 for details).

[0155] Table 2

[0156] Experimental group Elastic modulus (kPa) Degradation time point (week) Remaining mass (%) Example 1 95 0 100 Comparative Example 2 55 1 95 Example 1 88 2 80 Comparative Example 2 62 4 72 Example 1 90 6 65 Comparative Example 2 52 8 50 Example 1 92 1 98 Comparative Example 2 58 2 77

[0157] Experiment summary:

[0158] In Experiment 2, the physical properties of the hydrogel were optimized by adjusting the ratio of N-vinyl pyrrolidone (NVP) to polyethylene glycol diacrylate (PEGDA). The mechanism of this process involves changes in crosslinking density during polymerization. A high proportion of NVP leads to an increase in the degree of crosslinking between polymer chains, significantly affecting the elastic modulus and mechanical strength of the final hydrogel; while a lower NVP ratio can provide better flexibility and adaptability. In this way, hydrogels suitable for different application requirements can be designed, such as high elasticity and fixed support required in soft tissue repair.

[0159] During polymerization, the dual initiation mechanism of light / heat plays a crucial role. The pre-photoinitiator generates free radicals under ultraviolet light, initiating the polymerization of NVP and PEGDA, forming preliminary polymer chains; subsequently, the action of thermal initiator further promotes the generation of free radicals, accelerating the chain growth process and crosslinking reaction. Due to the optimization of polymerization conditions, the formation of hydrogel can be quickly completed under mild conditions, which not only ensures the stability of biomaterials, but also effectively controls the progress of polymerization.

[0160] The experimental results show that adjusting the ratio of NVP to PEGDA not only precisely regulates the elastic modulus of the hydrogel, but also affects its biodegradability. In the degradation experiment, as the PEGDA proportion increases, the degradation rate of the hydrogel slows down, maintaining a longer service period. This phenomenon is attributed to the role of PEGDA as a crosslinking agent, which increases the network structure between polymer chains, thereby delaying the hydrolysis process. Such adjustment mechanism significantly enhances the adaptability of the hydrogel system to different biological application scenarios (such as skin filling and soft tissue repair), providing important ideas and basis for future clinical applications.

[0161] Experiment 3:

[0162] Purpose of the experiment:

[0163] The residual monomer content in Comparative Example 1 (hydrogel treated by dialysis) and Comparative Example 3 (hydrogel not treated by dialysis) was compared to confirm the effectiveness of the in vitro washing process in ensuring the safety of the hydrogel.

[0164] Experimental materials:

[0165] N-vinyl pyrrolidone (NVP);

[0166] Polyethylene glycol diacrylate (PEGDA);

[0167] Photoinitiator (Irgacure-2959);

[0168] Thermal initiator (ammonium persulfate);

[0169] Deionized water;

[0170] Chromatographic column and analytical equipment (such as GC or HPLC);

[0171] Dialysis bag;

[0172] Experimental steps:

[0173] Material preparation:

[0174] Prepare the hydrogel solution according to the formulation of Example 1 (10 parts of NVP, 1 part of PEGDA, 0.1 part of Irgacure-2959, and 60 parts of deionized water).

[0175] Prepare the hydrogel according to the formulation of Comparative Example 3 (same formulation, but without dialysis treatment).

[0176] pH adjustment:

[0177] Adjust the pH of the two prepolymer solutions to 6.5-7.5.

[0178] Polymerization reaction:

[0179] For Example 1, use dual initiation reaction of photopolymerization and thermal polymerization, polymerize the hydrogel for 5 minutes according to the previous conditions.

[0180] For Comparative Example 3, only use the same photoinitiation conditions for polymerization, without thermal polymerization.

[0181] Hydrogel preparation:

[0182] After the polymerization is completed, the hydrogel of Example 1 is placed in a dialysis bag and dialyzed in deionized water for at least 72 hours to remove unreacted monomers.

[0183] The hydrogel of Comparative Example 3 is not dialyzed and is ready for use.

[0184] Residual monomer test:

[0185] The residual monomer content in both hydrogels was analyzed using gas chromatography (GC) or high-performance liquid chromatography (HPLC).

[0186] A standard curve was prepared to determine the residual concentrations of NVP and PEGDA for each sample.

[0187] Data recording and analysis:

[0188] The data of residual monomer content were collected and tabulated for comparative analysis (see Table 3 for details).

[0189] Table 3

[0190] Experimental group NVP residual content (%) PEGDA residual content (%) Example 1 0.05 0.02 Comparative Example 3 0.15 0.10 Example 1 0.04 0.01 Comparative Example 3 0.20 0.12 Example 1 0.03 0.03 Comparative Example 3 0.18 0.15 Example 1 0.07 0.01 Comparative Example 3 0.22 0.09

[0191] Experiment summary:

[0192] In Experiment 3, the effectiveness of the dialysis process in improving the biological safety of hydrogels was further verified by evaluating the residual monomer content of the hydrogels from Example 1 and Comparative Example 3. During the preparation of hydrogels, N-vinyl pyrrolidone (NVP) and polyethylene glycol diacrylate (PEGDA) are polymerized through a dual initiation mechanism of light / heat, resulting in cross-linked polymer chains. However, after the polymerization reaction is complete, unreacted monomers and initiators may still exist in the hydrogel, affecting its biocompatibility and safety. Therefore, the removal of residual monomers is an important step to ensure the application of hydrogels in clinical practice.

[0193] During the dialysis process, the hydrogels are placed in dialysis bags, and unreacted small molecule monomers such as NVP migrate to the external soaking solution through the dialysis membrane using the principle of molecular diffusion. Due to the good hydrophilicity of the cross-linked network of the hydrogel in the simulated physiological environment, the exchange of water and small molecules can be quickly carried out, thereby effectively reducing the concentration of residual monomers in the hydrogel. This phenomenon is verified in the experimental data, i.e., the residual monomer content of the hydrogel of Example 1 is much lower than that of Comparative Example 3, showing the effectiveness of the dialysis treatment in removing harmful components.

[0194] The experimental results show that the hydrogels treated by dialysis not only significantly reduce the residual monomer content (less than 0.1%), but also maintain good mechanical properties and chemical stability, meeting the safety standards of biological materials. This strategy of combining optimized synthesis and post-processing processes lays the foundation for the widespread application of hydrogels in the medical field in the future. By controlling the polymerization reaction and subsequent washing steps, not only the biocompatibility of the hydrogel is improved, but also its application prospects in clinical applications are enhanced, providing important scientific basis for achieving safer and more effective biological materials.

[0195] Test Experiment 1:

[0196] Objective of the experiment:

[0197] To evaluate the soft tissue repair effect of the hydrogel prepared based on Example 1 in the subcutaneous defects of rats, specifically to observe the volume retention rate and inflammatory reaction within 12 months after injection.

[0198] Experimental materials:

[0199] Hydrogel prepared according to Example 1 (using a light / heat dual initiation system);

[0200] Wistar rats (6-8 weeks old, weighing about 250-300g);

[0201] Surgical instruments (surgical knife, scissors, etc.);

[0202] Volume measuring instrument (such as vernier caliper);

[0203] Normal saline;

[0204] Observation record table;

[0205] Experimental steps:

[0206] Animal selection and feeding:

[0207] Select 30 healthy Wistar rats and randomly divide them into two groups, one group is the experimental group (injected with hydrogel), and the other group is the control group (injected with normal saline).

[0208] Feed in a suitable environment, and ensure that the rats adapt to the environment for at least one week before the experiment.

[0209] Anesthesia and surgical preparation:

[0210] Use appropriate anesthetics (such as sodium pentobarbital) to anesthetize the rats.

[0211] Make a small incision in the rat under sterile conditions to create a standardized subcutaneous defect (about 1cm x 1cm).

[0212] Hydrogel injection:

[0213] Inject the hydrogel prepared based on Example 1 (prepared according to the method steps) into the subcutaneous defects of the experimental group rats, ensuring uniform filling.

[0214] The control group is injected with the same volume of normal saline.

[0215] Postoperative observation and care:

[0216] Observe all rats after surgery and record the situation within 24 hours after surgery, paying special attention to wound bleeding and infection.

[0217] Observe and record the wound healing and possible inflammatory reactions weekly, using appropriate scoring criteria (such as redness, exudation degree scoring).

[0218] Volume measurement and data recording:

[0219] Measure the volume of the defect at 1 week, 1 month, 3 months, 6 months, and 12 months after surgery, and record the changes.

[0220] Calculate the volume retention rate using the formula: Volume retention rate = (Remaining volume of defect / Initial volume) x 100%.

[0221] Data analysis:

[0222] Organize the observed data, calculate the volume retention rate at each time point, and analyze the tissue regeneration effect and inflammatory reaction of the hydrogel (see Table 4 for details).

[0223] Table 4

[0224]

[0225]

[0226] Experimental summary:

[0227] The hydrogel prepared based on Example 1 exhibits excellent effect in soft tissue defect repair, with high volume retention rate and good safety. This hydrogel material can provide effective support for soft tissue repair and has good application prospects, especially in the fields of wound repair and plastic surgery.

[0228] Test experiment 2:

[0229] Experimental purpose:

[0230] Evaluate the application effect of the hydrogel material prepared based on Example 1 in facial wrinkle filling, specifically observe the wrinkle improvement rate and effect maintenance time.

[0231] Experimental materials:

[0232] Hydrogel prepared according to Example 1 (using a light / thermal dual initiation system);

[0233] Syringe;

[0234] Clinical observation record table;

[0235] Imaging equipment (such as high-definition camera, convenient for recording before and after comparison);

[0236] Experimental steps:

[0237] Subject selection:

[0238] Recruit 30 volunteers who are willing to participate in the experiment, all of whom are adults with obvious facial wrinkles, and ensure that they meet the participation conditions (age, health status, not pregnant, etc.).

[0239] Informed Consent:

[0240] Explain the purpose, process, and possible risks of the experiment to the subjects, and ensure that all participants sign the informed consent form.

[0241] Material Preparation:

[0242] Prepare the hydrogel prepared in Example 1 in a sterile syringe for injection.

[0243] Injection Steps:

[0244] In a sterile environment, inject the hydrogel into the facial wrinkle area of each subject, ensuring uniform distribution, and adjust the injection amount according to the depth and area of the wrinkles.

[0245] Observation Time Nodes:

[0246] Follow up and evaluate at 1 week, 1 month, 3 months, 6 months, 12 months, and 18-24 months after injection.

[0247] Effect Evaluation:

[0248] At each follow-up, use video recording to record wrinkle changes, and let the subjects subjectively evaluate the improvement of the squeezed parts through a scale (such as wrinkle severity score).

[0249] Record the improvement rate and effect maintenance at each time point.

[0250] Data Recording and Analysis:

[0251] Collect the feedback and score data of the subjects, organize them into tables, and conduct statistical analysis (see Table 5 for details).

[0252] Table 5

[0253]

[0254] The hydrogel prepared based on Example 1 shows good clinical effect in wrinkle filling, with high wrinkle improvement rate and long effect maintenance time, good safety, no significant adverse reactions observed, and is suitable for popularization and application in the field of facial beauty.

[0255] Although embodiments of the present application have been shown and described, it will be understood by those of ordinary skill in the art that various changes, modifications, substitutions and alterations can be made without departing from the principles and spirit of the present application, and the scope of the present application is defined by the appended claims and their equivalents.

Claims

1. A soft tissue repair and wrinkle filling material based on a mixed hydrogel of N-vinyl pyrrolidone and polyethylene glycol diacrylate, characterized in that: Includes the following component materials in parts by mass: 10-25 parts of N-vinyl pyrrolidone; 1-10 parts of polyethylene glycol diacrylate; Initiator 0.1 part to 1 part; 60-150 parts of solvent.

2. The soft tissue repair and wrinkle filling material based on N-vinyl pyrrolidone and polyethylene glycol diacrylate mixed hydrogel according to claim 1, characterized in that: The concentration of the N-vinyl pyrrolidone is 10-25%, and the molecular weight of the polyethylene glycol diacrylate is 400-2000, and the concentration is 1-10%.

3. The soft tissue repair and wrinkle filling material based on N-vinyl pyrrolidone and polyethylene glycol diacrylate mixed hydrogel according to claim 1, characterized in that: The initiator includes a photoinitiator and a thermal initiator. The photoinitiator is Irgacure-2959, and the thermal initiator is ammonium persulfate. The mass ratio of the photoinitiator to the thermal initiator is 1-2:0.5-1.

4. The soft tissue repair and wrinkle filling material based on N-vinyl pyrrolidone and polyethylene glycol diacrylate mixed hydrogel according to claim 1, characterized in that: The solvent can be deionized water or phosphate buffer.

5. A process for preparing a soft tissue repair and wrinkle filling material based on a mixed hydrogel of N-vinyl pyrrolidone and polyethylene glycol diacrylate, wherein the soft tissue repair and wrinkle filling material based on a mixed hydrogel of N-vinyl pyrrolidone and polyethylene glycol diacrylate according to claims 1-4 is characterized in that: The following steps are involved: S1. Dissolve NVP, PEGDA and initiator in deionized water or phosphate buffer and adjust the pH to 6.5-7.5 to form a prepolymer solution; S2, forming a hydrogel by dual polymerization initiation of photopolymerization and thermal polymerization; S3, dialyzing the obtained hydrogel in deionized water or phosphate buffer for not less than 72 hours to remove unreacted monomers; S4. Freeze-dry the dialyzed hydrogel and sterilize it.

6. The process for preparing the soft tissue repair and wrinkle filling material based on N-vinyl pyrrolidone and polyethylene glycol diacrylate mixed hydrogel according to claim 5, characterized in that: In the step S2, the photopolymerization is specifically: the wavelength is 300-400nm, the intensity is 10-50mW / cm 2 Irradiate the prepolymer solution with ultraviolet light for 1-10 minutes to initiate polymerization reaction; The thermal polymerization specifically comprises: heating the prepolymer solution to 50-70° C. in a heating furnace, reacting for 1-4 hours, and initiating the polymerization reaction.

7. The process for preparing the soft tissue repair and wrinkle filling material based on N-vinyl pyrrolidone and polyethylene glycol diacrylate mixed hydrogel according to claim 5, characterized in that: In the step S4, freeze drying is performed below -40°C for 24-48 hours; The sterilization process includes: Sterilization by destroying microbial DNA through gamma rays; Sterilization is performed by injecting ethylene oxide in a closed space.

8. Use of the soft tissue repair and wrinkle filling material based on the N-vinyl pyrrolidone and polyethylene glycol diacrylate mixed hydrogel according to claims 1 to 4 in soft tissue defect repair and skin wrinkle filling.

Citation Information

Cited By

  • Vinyl pyrrolidone copolymer as well as preparation method and application thereof

    CN121471431A